APPLICATION OF ELECTROPHORESIS PROCEDURE IN COSMETOLOGY - Shokirova , Farangiz Shavkatovna; Xakimov , Dilshod Rustamovich; Khatamov , Ulugbek Altibaevich (Educational Research in Universal Sciences, 2024)
Electrophoresis procedure in cosmetology represents an innovative method of delivering active ingredients of cosmetic products into the deeper layers of the skin using an electric field. This article discusses the mechanism of action of electrophoresis, its advantages, and its application in modern cosmetology practice. The main aspects of using this procedure are discussed, including moisturizing and nourishing the skin, combating aging, reducing pigmentation, and treating acne. Electrophoresis is an effective tool in skin care and can be successfully used both independently and in combination with other cosmetic procedures to achieve optimal results.